Myeloid sarcoma: an uncommon presentation of myeloid neoplasms; a case series of 4 rare cases reported in a tertiary care institute - Jadhav, Toyaja; Baveja, Puneet; Sen, Arijit (Autopsy and Case Reports, 2021)
Myeloid sarcoma (MS) is a rare extramedullary neoplasm of myeloid cells, which can arise before, concurrently with, or following hematolymphoid malignancies. We report 04 such cases of MS, diagnosed in this institute over a period of 6 years, during various phases of their respective myeloid neoplasms/leukemias. These cases include MS occurring as a relapse of AML (Case 1), MS occurring as an initial presentation of CML (Case 2), MS occurring during ongoing chemotherapy in APML (Case 3), and MS presenting as a progression of MDS to AML (Case 4). In the absence of relevant clinical history and unemployment of appropriate immunohistochemical (IHC) studies, these cases have a high risk of being frequently misdiagnosed either as Non-Hodgkin’s Lymphoma (NHL) or small round cell tumors or undifferentiated carcinomas, which may further delay their management, making an already bad prognosis worse. This case series has been designed to throw light on the varied presentation of MS and the lineage differentiation of its neoplastic cells through the application of relevant IHC markers along with their clinical correlation.